BROTHERHOOD/UKHWAH IN ISLAMIC PERSPECTIVE - Kamaluddin; Gustina Siregar (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
Human nature cannot live alone, he needs other people for his survival. Without other people a person will have no meaning whatsoever, that's why Islam forbids its people to separate themselves from the jama'ah (group). Human perfection as a servant of Allah, is not enough to just worship Allah alone (hamlum minallah), but is required to maintain harmonious relations (ukhwah) between fellow human beings (hablum minannas). If someone claims to believe in Allah and the Last Day (Judgment), he should glorify his neighbors or neighbors (al-Hadis). Therefore in Islam developed 3 forms of brotherhood (ukhwah), namely: a. Ukhwah Islamiyah, b. Ukhwah Basyariyah, c. Ukhwah Wathaniyah.